Regional to large‐scale mechanisms controlling intraseasonal variability of low‐level clouds in Western Equatorial Africa - (:unkn) unknown (My University, 2025)
The intraseasonal variability (ISV) of the stratiform cloud cover over Western Equatorial Africa (WEA) is analysed during the dry season (June-September, JJAS 1971-2019). Each JJAS daily sequence of a regional-scale index of the stratiform cloud cover could be assimilated as a red-noise process, without any significant recurrent periodicities. At local scale, cloudier conditions than usual are preceded by and synchronised with sustained easterly wind and warm anomalies near the top (850 hPa) and above the stratiform cloud deck, indicating higher stability. Anomalous easterlies or northeasterlies bring also anomalously moist air from either the Congo Basin or the West-African rainbelt region to WEA. At low levels (<850 hPa), there is a clear switch between antecedent warm easterlies and synchronous cool and dry westerlies from the cold-tongue area over the equatorial Atlantic. This switch may reflect a negative feedback loop, operating on a short time-scale (i.e., ∼3-5 days) and involving low-level thermal and geopotential gradients, zonal winds between the cold-tongue area and the Congo Basin, as well as the deep convection over the latter region. Kelvin waves appear to be a possible trigger of this loop, which could be sustained internally. Another main process operates at longer time-scales (i.e., ∼6-10 days) and involves a near-standing Rossby wave over the South Atlantic and adjacent southern Africa. A ridge over the central South Atlantic and downstream trough over southern Africa lead to an overall strengthening of the St. Helena high, and increased thermal and geopotential gradients between the southeast South Atlantic and southern Africa. The ridge-trough couple is also related to an anomalous warming over equatorial Africa in the middle troposphere associated with increased lower-tropospheric stability over WEA a few days later. All these mechanisms contribute to the knowledge regarding the intraseasonal atmospheric variations o
Keywords: African Research